Implementation of Prophetic Education in Islamic Boarding School (Pesantren) - M. Asep Fathur Rozi (Tarbiyah Departement collaboration with AMCA, 2018)
The prophetic value in question is humanist, liberation, transcendence in accordance with Kuntowijoyo's Prophetic Social Sciences (ISP)1 theory. The Pesantren Institution in question is the Pesantren for Children, Student Pesantren, Colleger Pesantren (PESMA), Campus Pesantren, Ma'had Ali Pesantren, Pesantren Takhassus, Pesantren Al-Qur'an, Language Pesantren, Skills Pesantren, Pesantren Kilat, Pesantren Ramadhan, Rehabilitation Pesantren, Worker‟s Pesantren, Virtual Pesantren in the book Dimensi Manajemen Pendidikan Islam by Mujamil Qomar. Prophetic implementation in Pesantren education institutions lies in the teaching and learning system that not only uses classical but with various methods that can foster a feeling of relying on God. The result is that the concept of Prophetic Social Science (ISP) Kuntowijoyo when implemented in Pesantren education institutions. This implementation actually seems to be forced on the level of the Pesantren Salaf. Because without using ISP theory, actually in their daily practices, communication patterns and also interactions that are built in the Pesantren Salaf have reflected the ISP theory itself.